2018
DOI: 10.1111/jam.13754
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and virulence traits ofEscherichia coliandSalmonellastrains isolated from vegetables and fruits from India

Abstract: The present study provides valuable baseline information that E. coli and Salmonella may use plants as an alternative host with significant clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
5
14
6
2
Order By: Relevance
“…In the present study, the recovery rate of E. coli (9.2 %) from leafy greens is consistent with other worldwide findings that reported the prevalence of E. coli in fresh produce, including leafy greens, within a range of 5.3-16.7% [10,22,24,40]. However, Salmonella contamination (6.5 %) of leafy greens in the present study ranged between 1.8 and 10%, as reported in previous studies on vegetable samples [22,24,41]. However, little information is available on DEC isolates from fresh produce [42,43], especially leafy greens [40].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the recovery rate of E. coli (9.2 %) from leafy greens is consistent with other worldwide findings that reported the prevalence of E. coli in fresh produce, including leafy greens, within a range of 5.3-16.7% [10,22,24,40]. However, Salmonella contamination (6.5 %) of leafy greens in the present study ranged between 1.8 and 10%, as reported in previous studies on vegetable samples [22,24,41]. However, little information is available on DEC isolates from fresh produce [42,43], especially leafy greens [40].…”
Section: Discussionsupporting
confidence: 92%
“…Emergence and spread of multi-drug resistance in bacterial pathogens, globally, constitute a nurturing threat to public health (Laxminarayan et al, 2013). Over the past few years, significant evidences have emerged worldwide showing the origin of MDR in the population of food-borne bacteria of animal agriculture (Doyle, 2015), as well as of fresh produce (Verma, Saharan, Nimesh, & Singh, 2018), which is in concurrence with bacteria of clinical settings (Laxminarayan et al, 2013). In the present study, MDR of different patterns was observed both for gram-negative (E. coli, Salmonella spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 and 3 show rdar morphotype was expressed by 18 (78.3%) isolates of E. coli (SMDS2, SMDS4, WMDS, SMKG1, SMKG2, SMKG3, SMKG4, SMKB2, SMKB4, SMKB5, SMKB8, SMK2, SMK3, SMU2, SMT4, WMSK4, WMSK7 and WMPP2) and rdar morphotypes absent in all Salmonella enterica. Verma et al (2018) reported that rdar morphotype characterized by both expressions of curli fimbriae and cellulose production was identified in 28 isolates (38.3%) of E. coli isolated from fresh vegetables and fruits samples.…”
Section: Colony Morphology Testmentioning
confidence: 99%
“…In another study, a higher percentage of saw morphotype was observed. It was found that 9 isolates (12.3%) of E. coli isolated from fresh vegetables and fruits sample did not bind with congo red dye and declared as negative (Verma et al, 2018).…”
Section: Colony Morphology Testmentioning
confidence: 99%